NURSING CARE OF CONTINUOUS URINARY INCONTINENCE IN THE ELDERLY POST-ISCHEMIC STROKE A CASE REPORT - Tyas, Anestasia Pangestu Mei; Arisandy, Fatimahndya Maulitha De; Ilkafah, Ilkafah; Mardhika, Amellia; Sulpat, Emuliana (Journal of Vocational Nursing, 2022)
Introduction : Continuous urinary incontinence is the continued and uncontrolled passing of urine without distension and a feeling of fullness in the bladder due to neurological dysfunction. This condition is often found in the elderly post-ischemic stroke. The study aimed to describe nursing care of continuous urinary incontinence in the elderly post-ischemic stroke in Lamongan. Methods : This study used a case study approach (case report) on a participant through the nursing process approach. The sample in this study is one patient, an elderly post-ischemic stroke. This research was conducted in 2021 in Lamongan with three visits to patients' homes for seven days. Data collection techniques include interviews, observation, and physical examination. This research instrument uses the gerontic nursing care format and sandvik severity index. Results : Continuous urinary incontinence nursing care with the main intervention for urinary incontinence treatment (I.04163) and the supporting intervention is pelvic muscle exercises (I.07215) can be applied to elderly post-ischemic stroke according to the expected outcomes. The continuous urinary incontinence has a partially resolved on the third home visit. The client can hold urine several times when the bladder feels full, reduced the frequency of night urination, and rarely wakes up because of wet diapers. Sandvik Severity Index shows a value of 4 (moderate incontinence). Conclusions: Improving nursing care need for collaboration between patients, families, and health workers in performing pelvic muscle exercises independently, continuously, and regularly to increase the strength of the detrusor-sphincter muscles and showed improvement in urinary continence.